The European landscape on allogeneic haematopoeietic cell transplantation in Chronic Lymphocytic Leukaemia between 2009 and 2019: a perspective from the Chronic Malignancies Working Party of the EBMT - Tournilhac, Olivier; van Gelder, Michel; Eikema, Dirk-Jan; Zinger, Nienke; Dreger, Peter; Bornhäuser, Martin; Vucinic, Vladan; Scheid, Christof; Cornelissen, Jan J; Schroeder, Thomas; Jindra, Pavel; Sengeloev, Henrik; et al. (Bone marrow transplantation, 2023)
Allogeneic transplantation (allo-HCT) is a curative treatment in CLL whose efficacy including the most severe forms had led to the 2006 EBMT recommendations. The advent after 2014 of targeted therapies has revolutionized CLL management, allowing prolonged control to patients who have failed immunochemotherapy and/or have TP53 alterations. We analysed the pre COVID pandemic 2009-2019 EBMT registry. The yearly number of allo-HCT raised to 458 in 2011 yet dropped from 2013 onwards to an apparent plateau above 100. Within the 10 countries who were under the EMA for drug approval and performed 83.5% of those procedures, large initial differences were found but the annual number converged to 2-3 per 10 million inhabitants during the 3 most recent years suggesting that allo-HCT remains applied in selected patients. Long-term follow-up on targeted therapies shows that most patients relapse, some early, with risk factors and resistance mechanisms being described. The treatment of patients exposed to both BCL2 and BTK inhibitors and especially those with double refractory disease will become a challenge in which allo-HCT remains a solid option in competition with emerging therapies that have yet to demonstrate their long-term effectiveness.
Keywords: Neoplasm Recurrence, Local; Transplantation, Homologous; Leukemia, Lymphocytic, Chronic, B-Cell; homologní transplantace; lidé; retrospektivní studie; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; Retrospective Studies; chronická lymfatická leukemie; COVID-19; lokální recidiva nádoru; Transplantation Conditioning; Humans